Saving for Retirement Without Harming Others - Daskal, Steven (2013)
This article discusses moral issues raised by defined contribution retirement plans, specifically 401(k) plans in the United States. The primary aim is to defend the claim that the federal government ought to require 401(k) plans to include a range of socially responsible investment (SRI) options. The analysis begins with the minimal assumption that corporations engage in behavior that imposes morally impermissible harms on others with sufficient regularity to warrant attention. After motivating this assumption, I argue that individual investors typically share in the responsibility for the harms imposed by corporations in which they invest, and that they therefore have a moral obligation to incorporate considerations of social responsibility into their investment decisions, when possible, to avoid being complicit in morally impermissible corporate behavior. I further argue that individuals are subject to substantial institutional and structural pressures that create a powerful incentive to invest in 401(k) plans, even though such plans typically lack any SRI options. To eliminate this pressure to commit indirect harm in the process of saving for retirement, I recommend that the federal government requires 401(k) plans to incorporate a range of SRI options, and I defend this proposal from several possible objections.
Keywords: Defined contribution; Ethical Investing; mutual funds; 401(k); Retirement savings; Socially Responsible Investment